Socio-cognitive scaffolding with collaboration scripts: a meta-analysis - Vogel, Freydis; Wecker, Christof; Kollar, Ingo; Fischer, Frank (Springer, 2017)
Scripts for computer-supported collaborative learning (CSCL) offer socio-cognitive scaffolding for learners to engage in collaborative activities that are considered beneficial for learning. Yet, CSCL scripts are often criticized for hampering naturally emerging collaboration. Research on the effectiveness of CSCL scripts has shown divergent results. This article reports a meta-analysis about the effects of CSCL scripts on domain-specific knowledge and collaboration skills. Results indicate that CSCL scripts as a kind of socio-cognitive scaffolding can enhance learning outcomes substantially. Learning with CSCL scripts leads to a small positive effect on domain-specific knowledge (d = 0.20) and a large positive effect on collaboration skills (d = 0.95) compared to unstructured CSCL. Further analyses reveal that CSCL scripts are particularly effective for domain-specific learning when they prompt transactive activities (i.e., activities in which a learner’s reasoning builds on the contribution of a learning partner) and when they are combined with additional content-specific scaffolding (worked examples, concept maps, etc.). Future research on CSCL scripts should include measures of learners’ internal scripts (i.e., prior collaboration skills) and the transactivity of the actual learning process.